Research Advances in the Application of the Supercritical CO[sub.2] Brayton Cycle to Reactor Systems: A Review - Xiao, Yuhui; Zhou, Yuan; Yuan, Yuan; Huang, Yanping; Tian, Gengyuan (Energies (Basel), 2023)
Amid the global emphasis on efficient power conversion systems under the “dual carbon” policy framework, the supercritical CO[sub.2] (SCO[sub.2]) Brayton cycle is a noteworthy subject, owing to its pronounced efficiency, compact design, economic viability, and remarkable potential to increase the thermal cycle efficiency of nuclear reactors. However, its application across various nuclear reactor loops presents divergent challenges, complicating system design and analytical processes. This paper offers a thorough insight into the latest research on the SCO[sub.2] Brayton cycle, particularly emphasising its integration within directly and indirectly cooled nuclear reactors. The evolution of the Brayton cycle in nuclear reactor systems has been meticulously explored, focusing on its structural dynamics, key components, and inherent pros and cons associated with distinct reactor loops. Based on the theoretical frameworks and empirical findings related to turbomachinery and heat exchangers within the cycle, we chart a course for future enquiries into its critical components, underscoring the indispensable role of experimental investigations. This paper conclusively assesses the feasibility of deploying the SCO[sub.2] Brayton cycle in direct and indirect cooling contexts, offering a forward-looking perspective on its developmental trajectory. The SCO[sub.2] Brayton cycle may become a focal point for research, potentially creating avenues for nuclear energy endeavours.